2017
DOI: 10.1186/s41065-017-0031-7
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of differentially expressed genes and adaptive mechanisms of Prunus triloba Lindl. under alkaline stress

Abstract: Background Prunus triloba Lindl. is a naturally salt-alkaline-tolerant plant with several unique characteristics, and it can be used as the rootstock of Chinese plum (Prunus salicina Lindl.) in saline-alkaline soils. To comprehensively investigate the alkaline acclimation mechanisms in P. triloba, a series of analyses were conducted under alkaline stress, including analyses of the kinetics of molecular and physiological changes, and leaf microstructure.ResultsTo understand the kinetics of molecular changes und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 38 publications
(41 reference statements)
0
8
0
Order By: Relevance
“…In peach, comparative transcriptome analysis of roots of GF677 and Maotao suggests osmotic pressure increase and redox balance are crucial for GF677 response to saline-alkaline stresses [16]. Leaf chlorosis usually acts as an early symptom of this stress [10,11]. Our previous research showed that the photosynthetic rate was significantly higher in the leaves of GF677 than in Maotao [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In peach, comparative transcriptome analysis of roots of GF677 and Maotao suggests osmotic pressure increase and redox balance are crucial for GF677 response to saline-alkaline stresses [16]. Leaf chlorosis usually acts as an early symptom of this stress [10,11]. Our previous research showed that the photosynthetic rate was significantly higher in the leaves of GF677 than in Maotao [21].…”
Section: Discussionmentioning
confidence: 99%
“…), black locust (Robinia pseudoacacia L.), and Chinese plum (Prunus salicina Lindl. ), and thousands of differentially expressed genes have been detected [8][9][10][11].…”
mentioning
confidence: 99%
“…RNA-seq approach has been employed to study gene expression in response to drought and salinity in the roots of Prunus mahaleb and Prunus persica 27 . The dynamics of gene expression in leaves in response to alkaline stress has been reported in Prunus triloba Lindl 28 . In addition, water use efficiency-related genes have been identified in the roots of the almond-peach rootstock ‘Garnem’ by employing time-course transcriptome analysis 29 .…”
Section: Introductionmentioning
confidence: 99%
“…Microarrays, the most widely used transcriptomics technology for many years, are being replaced by RNA-seq too, which is becoming the dominant technology today [47,48], due to the higher sensitivity and cost accessibility. Although RNA-seq analyses that rely on already sequenced and assembled genomes provide robust results [47,48,[149][150][151][152][153][154][155], RNA-seq suitably supports transcriptome-based analyses also of non-model species [156][157][158][159][160][161][162][163][164][165][166][167][168]. The knowledge of the analyzed genome is not a prerequisite for the analyses, providing a consistent representation of the transcriptome content in comparison to the microarray technology, thanks to its powerful throughput.…”
Section: Transcriptomicsmentioning
confidence: 99%